Resonant tunnelling diode optoelectronic receivers and transmitters - Alomari, Saif Asem Yasin (2022)
This thesis describes the research work on double barrier quantum well (DBQW) resonant tunneling diode (RTD) based optoelectronic transmitters and receivers, focused on the design and characterization of resonant tunneling diode photodetectors (RTD-PD) implemented in the In53Ga47As/InP material system for operation at 1.55 μm and 1.31 μm wavelengths, and evaluate numerically the merits of the integration of an RTD/RTD-PD with a laser diode (LDs) to act as simple optoelectronic transmitters. The aim of the work was to investigate simple, low-cost, high-speed transmitter and receiver architectures taking advantage of RTDs properties such as the structural simplicity, high frequency (up to terahertz), and wide-bandwidth built-in electrical gain (roughly, from dc to terahertz). Also described are the preliminary studies of RTD-PDs operation as single photon detector at room temperature utilizing the excitability property. In this work, we evaluate which factors affect the bandwidth of RTD-PDs. Knowing the answer to this, we propose rules and optimizations necessary to achieving high bandwidth (>10 GHz) RTD-PDs. Furthermore, we show how to utilize the built-in amplification, arising from the RTD non-linear current-voltage (IV) curve and the presence of a negative differential resistance region (NDR) to building high responsivity photodetectors that can outperform current commercial technologies, particularly PIN photodiodes, in novel applications. The design and modeling work relied on numerical simulations utilizing the nonequilibrium Green’s function formalism (NEGF), which we implement using Silvaco ATLAS. We briefly introduce the NEGF method and Silvaco ATLAS and utilize them to do the design of the epitaxial structure of novel devices. The results of which are novel models which allow us to predict the effect that the RTD structural parameters (doping concentration and the lengths of both the emitter and collector) have on the peak voltage of the RTD. We study experimentally the factors affecting the bandwidth by optical characterization of several epitaxial layer stacks and propose hypotheses that help to explain the measured bandwidths. We show that for high-speed RTD-PDs (sub nanosecond), the light absorption layers should be confined to the locations where the electric field is sufficiently high and avoiding highly doped thick contact layers with band gap energies below the energy of the photons being detected. Additionally, we outline a set of rules for the design of RTD-PD detectors based on ni-n and p-i-n heterostructures, where the length, location, and doping level of the absorption regions are the relevant parameters to be considered in determining the bandwidth and responsivity of the devices. Moreover, we measure and report on the responsivity of RTDPDs under both DC and AC optical excitation. We show that RTD-PDs can have very high responsivity values reaching up to 1×107 A/W, and electrical bandwidth of around 1.26 GHz (1.75 GHz optical) that is limited by the lifetime of the photo-generated minority carriers (the holes). The last part of the thesis is dedicated to the study of RTD-PD circuits, where the integration between an RTD-PD and a laser diode (LD) is thoroughly examined. The LD acts as a load that is driven by the RTD-PD current. We derive and investigate the equivalent circuit for such a system incorporating the Schulman function for the RTD-PD IV, using the solution to study several operation regimes using MATLAB code. These regimes include the RTD-PD biased in the positive differential resistance region (PDR), when it is biased in the NDR region, and when induced to switch between the PDR and NDR regions. We also show how the excitability property of the RTD-PD can be used for detecting very low signal intensity levels, and the ability of RTDs to operate as voltage-controlled oscillators while biased in the NDR region.